Endoscopic diagnosis and treatment of complete anastomosis stenosis after colorectal resection without protective ileostomy: report of two cases and literature review - Deng, Shenghe (J Int Med Res, 2020)
This case report describes a novel procedure for opening the lumen of a completely obstructed anastomosis when open surgery is not an option. Two patients underwent ileocecal or colorectal resection and one-stage anastomosis reconstruction without diverging ileostomy. The patients developed post-surgical abdominal distension and nausea. Emergency imaging indicated complete anastomotic obstruction and distal intestinal anastomosis emptiness. Colonoscopy revealed an anastomosis that was completely discontinued by a membranous structure. Considering that open surgery was not a viable treatment option, a minimally invasive endoscopic approach was adopted to repair the obstruction. A needle knife was used to puncture the linear white scar and contrast agent was injected under endoscopy and fluoroscopic guidance. Fluoroscopically, the proximal bowel was identified and a dual knife-mediated membrane puncture was performed. A guidewire was then passed through the incision into the proximal bowel and progressive pneumatic dilatation was performed successively with a controlled radial expansion balloon dilator until a 1.8 cm diameter dilation was achieved. After conventional balloon dilatation, the endoscope easily passed through the anastomosis without any patient discomfort. There were no postoperative signs of immediate or delayed complications. Overall, endoscopic incision and dilatation was a safe and effective treatment for acute anastomotic obstruction after colorectal surgery.